2019
DOI: 10.3389/fmicb.2019.02822
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rumen Protozoa by Specific Inhibitors of Lysozyme and Peptidases in vitro

Abstract: Defaunation studies have shown that rumen protozoa are one of the main causes of low nitrogen utilization efficiency due to their bacterivory and subsequent intraruminal cycling of microbial protein in ruminants. In genomic and transcriptomic studies, we found that rumen protozoa expressed lysozymes and peptidases at high levels. We hypothesized that specific inhibition of lysozyme and peptidases could reduce the activity and growth of rumen protozoa, which can decrease their predation of microbes and proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Collectively, the reduced expression of LYZ enzymes may imply that most artificially dosed microorganisms from the donor cow colonized in the rumen successfully, instead of being digested in the abomasum. On the other hand, lower lysozymes could reduce the activity and growth of rumen protozoa, which are one of the main causes of inefficient nitrogen use in cattle [ 60 ]. Dosing may be a potentially meaningful approach to improve the feed efficiency in cattle at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the reduced expression of LYZ enzymes may imply that most artificially dosed microorganisms from the donor cow colonized in the rumen successfully, instead of being digested in the abomasum. On the other hand, lower lysozymes could reduce the activity and growth of rumen protozoa, which are one of the main causes of inefficient nitrogen use in cattle [ 60 ]. Dosing may be a potentially meaningful approach to improve the feed efficiency in cattle at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…Methanogens attached to the cilia of enteric protozoa can be indirectly removed if protozoa are removed from the rumen 104 . Although protozoa removal can reduce up to 42 percent of methane emissions in cattle 105 , defaunation also disturbs beneficial microorganisms, impairing digestion and animal performance [106][107][108][109][110] . Despite being among the oldest proposed enteric methane mitigation strategies, defaunation requires complex experimental procedures (i.e.…”
Section: Inhibition Of Methanogenic Communities In the Rumenmentioning
confidence: 99%
“…Despite being among the oldest proposed enteric methane mitigation strategies, defaunation requires complex experimental procedures (i.e. isolation of newborns, or fistulating adults) and no practical and sustainable method is available 104,107,108,111 .…”
Section: Inhibition Of Methanogenic Communities In the Rumenmentioning
confidence: 99%
“…However, further investigation is required. In vitro studies utilizing both ciliate monocultures and rumen fluid inocula have shown that restraining protease activities, while not limited to ruminal ciliates, could enhance NUE without adverse effects on ruminal fermentation and digestion [ 89 , 90 ]. Approaches such as selecting target enzymes specific to ruminal ciliates, screening feed additives with anti-protozoal properties, and adjusting rumen passage rates are also worthy of consideration.…”
Section: Introductionmentioning
confidence: 99%